Two new cave-dwelling species of Tyrannochthonius Chamberlin 1929 (Pseudoscorpiones: Chthoniidae) from the Guizhou karst, China - Gao, Zhizhong; Zhang, Feng; Chen, Huiming (Zootaxa, 2020)
Two new troglomorphic pseudoscorpion species, Tyrannochthonius harveyi, sp. nov. and Tyrannochthonius zhai, sp. nov., are described from the dark zone of caves in the tower karst of the Guizhou Province in China. Both species are presently known only from single caves and are likely to have very restricted distribution ranges.